Teachers’ Objectives in Teaching Literature The Case of Literature Teachers at Foreign Languages Departments University of Laghouat - BOUKENS, Hanane; LARABA ,Nadia; GASMI ,Mustapha (Faculty of Letters and Foreign Languages Department of English, 2019)
A literature should be taught for many reasons and various objectives at the same time students have their own interests and needs that have to be bearing in mind. This study is an attempt to set aims and objectives of university foreign languages literature teachers and identify the way to make them attainable. The research is based on a questionnaire as an instrument to test the research hypotheses, which was answered by 14 literature teachers of foreign languages. It was described and interpreted through the quantitative and qualitative approaches. Through our own interpretations and data analysis, we have found that students who are motivated by their own desires and wants can do better in learning that is why teachers have to exploit literature to obtain various aims by selecting literary works and adapt their teaching according to students’ needs to create a successful class. It is suggested that opening discussions among students and tolerate different interpretations that may be opposed to teachers’ opinions will increase creativity and form future researches, as well as, literary texts which cope with the wants of students facilitate learning process